PENGARUH LOVE OF MONEY, MACHIAVELLIAN, RELIGIUSITAS DAN IDEALISME TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNISNU JEPARA - Vena Hawinatul Roifa; Isyfa Fuhrotun Nadhifah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
Students ethical perceptions will significantly determine their views on the ethics of the accounting profession in the future. Everyone has their own reasoning, morals, and perspectives, so education during college does not guarantee a person will become a good accountant. The sample in this study was 79 respondents from accounting students at the Faculty of Economics and Business, UNISNU Jepara. The results of this study indicate that Love of Money has no effect on accounting students ethical perceptions. Machiavellianism has a significant negative effect on accounting students ethical perceptions. Religiosity has no effect on accounting students ethical perceptions. Idealism does influence accounting students ethical perceptions.